Interfacial Dzyaloshinskii-Moriya interaction arising from rare-earth orbital magnetism in insulating magnetic oxides - Lucas Caretta (Nature Portfolio, 2020)
The origin of interfacial Dzyaloshinskii-Moriya interaction (iDMI) in insulating magnetic oxides remains unclear. Here, Caretta et al. find that an intrinsic spin-orbit coupling due to rare-earth orbital magnetism generates iDMI at mirror symmetry-breaking interfaces of magnetized iron garnets Tm3Fe5O12.